Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1104/pp.19.00483
|View full text |Cite
|
Sign up to set email alerts
|

Impaired PSII Proteostasis Promotes Retrograde Signaling via Salicylic Acid

Abstract: Photodamage of the PSII reaction center (RC) is an inevitable process in an oxygen-rich environment. The damaged PSII RC proteins (Dam-PSII) undergo degradation via the thylakoid membrane-bound FtsH metalloprotease, followed by posttranslational assembly of PSII. While the effect of Dam-PSII on gene regulation is described for cyanobacteria, its role in land plants is largely unknown. In this study, we reveal an intriguing retrograde signaling pathway by using the Arabidopsis (Arabidopsis thaliana) yellow vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 70 publications
1
52
0
Order By: Relevance
“…Besides D1, the D2 protein of the PSII RC also exhibits a decline upon a 1 O 2 burst, indicating probable photodamage of D2 by 1 O 2 (Koivuniemi et al, 1995;Jansen et al, 1999;Edelman and Mattoo, 2008). In accordance, recent studies have demonstrated that the oxidative modification is not limited to D1, but rather all PSII RC proteins including D2, CP43, and CP47 get oxidized by 1 O 2 (Dreaden Kasson et al, 2012;Dogra et al, 2019a;Dogra et al, 2019b;Duan et al, 2019). Though these oxidative modifications might be linked with the turnover, the precise relevance of these modifications in PSII proteins needs to be investigated.…”
Section: Psii Damagesupporting
confidence: 66%
“…Besides D1, the D2 protein of the PSII RC also exhibits a decline upon a 1 O 2 burst, indicating probable photodamage of D2 by 1 O 2 (Koivuniemi et al, 1995;Jansen et al, 1999;Edelman and Mattoo, 2008). In accordance, recent studies have demonstrated that the oxidative modification is not limited to D1, but rather all PSII RC proteins including D2, CP43, and CP47 get oxidized by 1 O 2 (Dreaden Kasson et al, 2012;Dogra et al, 2019a;Dogra et al, 2019b;Duan et al, 2019). Though these oxidative modifications might be linked with the turnover, the precise relevance of these modifications in PSII proteins needs to be investigated.…”
Section: Psii Damagesupporting
confidence: 66%
“…Among them, FtsH2 and FtsH5 are pivotal for establishing a functional FtsH protease, as evident in the emergence of leaf variegation in the cognate mutant plants (Yu et al, 2005). Besides, the loss of FtsH2 results in the accumulation of damaged PSII proteins relative to wild-type plants and in the failure of survival under very mild light stress conditions wherein wild-type plants can rapidly acclimate (Duan et al, 2019). Not only PSII proteins but also other chloroplast proteins appear to accumulate in the chloroplasts of var2 mutant lacking FtsH2.…”
Section: Damaged/unfolded/misfolded Protein Responses Via Rsmentioning
confidence: 99%
“…Intriguingly, one var2 allele, var2-9, was found to upregulate not only a suite of genes involved in PQC but also salicylic acidresponsive genes (SRGs) (Duan et al, 2019). var2-9 mutant plants express dysfunctional FtsH2, which specifically impairs the substrate unfolding activity.…”
Section: Damaged/unfolded/misfolded Protein Responses Via Rsmentioning
confidence: 99%
“…24,25 Thus, 1 O 2 generation and PSII damage are considered as default processes during photosynthesis, which tend to increase under photo-oxidative stress conditions. 21,22,26 The damaged PSII continually undergoes a repair process at the non-appressed regions of the thylakoids. The degradation of the damaged PSII RC proteins such as D1 by the FtsH protease is required to promote PSII reassembly.…”
Section: Loss Of Ftsh2 Induces a Damaged Protein Responsementioning
confidence: 99%
“…21 Moreover, the reinforced PSII proteostasis and the accumulation of damaged proteins appear to promote SA synthesis via the chloroplast-established isochorismate (ICS) pathway. 22 This finding suggests a potential interconnection between the impaired proteostasis (or its related problem such as altered redox status) and the stimulation of the ICS pathway.…”
Section: Introductionmentioning
confidence: 99%